A cross-sectional study on the reasons for vaccine hesitancy in children under seven years of age in Isfahan, Iran - Negar Farajzadeh; Habibollah Hosseini; Mahrokh Keshvari; Mohammad R. Maracy (Vaccine: X, 2023)
Introduction: The diminution in vaccination coverage in recent years has contributed to the reappearance of infectious diseases, and vaccine hesitancy is one of the main causes. As a result, we investigated the causes of vaccine hesitancy in children. Materials and methods: This descriptive-analytical study was conducted cross-sectionally in 27 comprehensive health service centers in Isfahan City from June to October 2022. This study included Iranian families living in Isfahan who did not vaccinate their children by the due date. A researcher-made questionnaire collected data on children's vaccine hesitancy after verifying validity and reliability over the phone and in person by the researcher. The mothers completed informed consent. Independent T-tests, Pearson's correlation coefficient, analysis of variance, and a generalized linear model were used to analyze the data. Findings: Finally, 298 families participated in the study, 34.3% refused, and 65.7% delayed their child's vaccination. Vaccination was hesitant due to the child being sick at the time of injection (57.3%), believing that vaccination is not necessary to prevent uncommon diseases (49%), and being concerned about severe side effects caused by the vaccine (48.7%). Vaccine hesitancy among mothers with bachelor's degrees and families less than one kilometer from the health center was significantly less than among others. Additionally, Vaccines at birth, four, six, twelve, and eighteen months, and six-year-old vaccines were associated with vaccine hesitancy. Conclusion: Children's illness at the time of vaccination, the belief that vaccination is unnecessary to prevent uncommon diseases, and the worry about severe complications were among the most common reasons for vaccine hesitancy. Mother's education, distance to the health center, and vaccine type were associated with vaccine hesitancy.